2012
DOI: 10.1167/iovs.12-9951
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping BeautyTransposon-Mediated Transfection of Retinal and Iris Pigment Epithelial Cells

Abstract: Transfection using the nonviral SB100X vector system avoids complications associated with viral gene delivery. SB100X-mediated transfer allows for stable PEDF gene integration into the cell's genome, ensuring continuous expression and secretion of PEDF. Stable expression of the therapeutic gene is critical for the development of cell-based gene addition therapies for retinal degenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 54 publications
5
44
0
1
Order By: Relevance
“…We previously showed that ratios ranging from 0.038 μg SB100X transposase expression plasmid DNA and 0.462 μg PEDF transposon plasmid DNA (1+12) to 0.017 μg SB100X transposase and 0.483 μg PEDF transposon (1+28) resulted in good transposition efficiencies, as determined by the secretion of recombinant PEDF 25 . Since transfection experiments with varying amounts of pFAR4-CMV SB100X SV40 transposase and pFAR4-ITRs CMV PEDF BGH (pFAR-PEDF) transposon miniplasmid DNA exhibited similar results, with the highest PEDF secretion rates observed for the ratios 1+16 and 1+20 (Figure S1), all subsequent experiments were carried out using 0.03 μg SB100X transposase expression plasmid DNA and 0.47 μg PEDF transposon plasmid DNA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that ratios ranging from 0.038 μg SB100X transposase expression plasmid DNA and 0.462 μg PEDF transposon plasmid DNA (1+12) to 0.017 μg SB100X transposase and 0.483 μg PEDF transposon (1+28) resulted in good transposition efficiencies, as determined by the secretion of recombinant PEDF 25 . Since transfection experiments with varying amounts of pFAR4-CMV SB100X SV40 transposase and pFAR4-ITRs CMV PEDF BGH (pFAR-PEDF) transposon miniplasmid DNA exhibited similar results, with the highest PEDF secretion rates observed for the ratios 1+16 and 1+20 (Figure S1), all subsequent experiments were carried out using 0.03 μg SB100X transposase expression plasmid DNA and 0.47 μg PEDF transposon plasmid DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Effective SB -mediated gene transfer has been reported for various in vitro and in vivo disease models,41, 42, 43 and it has been approved for clinical application of genetically modified T cells to treat B-lymphoid malignancies 44, 45. We have reported long-term and continuous PEDF secretion by RPE cells that were transfected with the PEDF transgene using the SB100X transposon system 25 and demonstrated that the subretinal transplantation of PEDF-transfected cells in a rat model of CNV reduces neovascularization and inhibits new vessel formation 46 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations